1996
DOI: 10.1002/bjs.1800830617
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of radial margins of clearance in rectal cancer

Abstract: A retrospective review of 325 patients was undertaken to analyse whether involvement of the radial resection margin (RRM) could predict locally recurrent disease or distant metastases in patients who had curative surgery for rectal or rectosigmoid cancer. Information on the RRM was available in 253 patients. The RRM was involved in 31 (12 per cent). Nine of these 31 patients developed local recurrence (29 per cent), while only 17 local recurrences were diagnosed in 217 patients (8 per cent) without involvement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
88
2
10

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(107 citation statements)
references
References 18 publications
7
88
2
10
Order By: Relevance
“…This is consistent with most studies on the prognostic prediction of CRM 6, 7, 8, 12, 13, 14, 15, 16…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with most studies on the prognostic prediction of CRM 6, 7, 8, 12, 13, 14, 15, 16…”
Section: Discussionsupporting
confidence: 92%
“…Many studies considered CRM as positive when it was ≤1 mm (R1) and associated with obviously poor prognosis as compared to CRM >1 mm (R0), which was in accordance with the ESMO guidelines 6, 8, 12, 13, 14, 15, 16, 17. The criterion to define a positive CRM remains unclear.…”
Section: Introductionmentioning
confidence: 75%
“…Several factors seem to determine tumor regression after preoperative radiotherapy, including fraction size and total dose applied. 25,32 In randomized studies with a dose of no more than 20 Gy, no downstaging or complete histological tumor regression was found. 24,32 Tumor regression was reported with a total radiation dose exceeding 20 Gy.…”
Section: Radiotherapy In Rectal Cancer (Bouzourene Et Al)mentioning
confidence: 99%
“…We first paid attention to factors known to adversely influence the risk of local recurrence or survival in rectal cancer treated with surgery alone, including such tumor characteristics as tumor stage, differentiation grade, tumor type, lymphatic or venous invasion, RRM, and clearance. 11,24,25 We also looked at the prognostic role of tumor regression in rectal cancers preoperatively treated by HART. We found in this study, as in a previously reported study, 10 that advanced pT was associated with a decreased DFS.…”
Section: Radiotherapy In Rectal Cancer (Bouzourene Et Al)mentioning
confidence: 99%
“…Apesar deste fato, o envolvimento da margem distal de ressecção está associado à recidiva local, sendo considerado a principal causa mencionada em algumas séries na literatura. (25,26,27,28) A taxa de ressecabilidade nas cirurgias para recidiva pélvica foi de 65,4%, próximo ao encontrado por Bedrosin e col. (29) , que verificaram aproximadamente 60% de ressecabilidade nestes casos, e superior ao referido por Boyle e col. (7) , (36,8%).…”
Section: Figura 1 -Cirurgias Realizadas Inicialmente Para Abordagem Dunclassified